G507(P) 'Let us speak' – Children's opinions of doctors. (24th May 2017) - Petrie, K; McArdle, A; Cookson, J; Powell, E; Poblete, X
Abstract : Aims: The Royal College of Paediatrics and Child Health states that a paediatrician must be 'sensitive, empathetic, persuasive' and 'good at communicating with a wide range of people' including children of various ages to parents and other family members. They must involve and empower children and young people (CYP) in consultations and decisions regarding their health. This is especially important for children diagnosed with complex, long-term conditions. As part of a longstanding educational collaboration between our Community Paediatrics Department and local schools, we designed a survey to explore what CYP think about doctors to determine whether we fulfil their expectations. Method: We designed a self-reporting questionnaire consisting of 8 Likert scale questions and one free-text response to be completed by children aged 7–16 years at local schools. The questions examined communication skills, empathy and interest in the concerns of CYP and their parents. Results: Our questionnaire was completed by 701 children. They reported: – 67% of doctors are interested in opinions of CYP; however, 87% of doctors are interested in opinions of parents/carers. – 70% of doctors understand the worries of CYP. – 48% are confident to talk to doctors. – 75% of doctors explain things appropriately. – 65% had seen a doctor in preceding six months Summary of qualitative data: CYP want to be listened to. They value a caring, knowledgeable doctor who gives them honest, clear explanations in a friendly and comfortable environment. They want to be spoken to by an approachable, smiling doctor and shown respect 'even on your night shift at 0630'. Conclusions: Our study suggests children feel doctors are more interested in their parent's opinions. They want to be listened to and spoken to directly instead of relying on parents/carers. They value age-appropriate, open consultations. The data demonstrates that children have strong opinions of doctors, often as a result of direct experience where poor experiences appeared to have lasting, negative impressions. Understanding these views will help doctors to address their concerns, empower them to provide their own histories and participate in decisions regarding their care.